Pengaruh Sakpole (Sistem Administrasi Kendaraan Pajak Online) terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Pemahaman Internet Sebagai Variabel Moderating - Ika Damayanti; Erma Setiawati (Syntax Idea, 2083)
This research aims to analyze and test the influence of the Online Vehicle Tax Administration System (SAKPOLE) on Taxpayer Compliance with internet understanding as a moderating variable. This research is quantitative research. The sampling technique used in this research is simple random sampling technique. The data used in this research is primary data by distributing questionnaires to users of the Online Vehicle Tax Administration System (SAKPOLE). The total sample used in this research was 164 respondents. The data analysis method used is a multiple linear regression model and analyzed using the SPPS version 21 program. The results of the research show that internet understanding has a positive and significant effect on the relationship between SAKPOLE and taxpayer compliance. So it is concluded that internet understanding is a moderating variable in the relationship between SAKPOLE and taxpayer compliance.